In vitro antitrichomonal activity of Satureja khuzestanica and main essential oil components carvacrol, thymol, and eugenol - Faezeh Karami; Dara Dastan; Mohammad Fallah; Mohammad Matini (Journal of Infection in Developing Countries)
Introduction: Human trichomoniasis is a widespread sexually transmitted disease and the concern of drug resistance in the parasite is growing. Hence, this study was performed to evaluate in vitro antitrichomonal activity of Satureja khuzestanica, carvacrol, thymol, eugenol, and phytochemical evaluation of the S. khuzestanica oil.